Mental health of survivors of 1984 Bhopal disaster: A continuing challenge - Murthy, R. Srinivasa (Ind Psychiatry J, 2014)
Bhopal disaster is an important milestone in Indian Industrial Psychiatry. The disaster was not only the biggest industrial disaster but also one in which complex forces have joined hands to demy the mental health needs of the population. Though the biggest general population epidemiological study over 5 years was carried out to understand the mental health impact of the disaster, the findings of this study did not get reflected in mental health care for the population. Furthermore, the needed longitudinal studies and evaluation of the interventions were not undertaken. There was no sharing of information with the survivors about the impact of the disaster on their health and well-being and sharing of skills for self-care. A result of these factors is the extreme degree of dissatisfaction in the population. Looking back, it would have met the needs of the Bhopal population, if the mental health services were community based and reaching the population, rather than the clinic-based approaches, there was a wide range of services, especially rehabilitation, continuous research into the changing mental health needs of the population and the effectiveness of interventions and most importantly, there was a continuous dialogue with the population and sharing of information with the general population. These are the tasks for the immediate future to reorganize the focus of mental health initiatives in Bhopal. Many lessons can be learnt from the Bhopal disaster and the continuing tragedy for the population.